2007
DOI: 10.1002/jcp.21270
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface protein detection with immunogold labelling in ESEM: Optimisation of the method and semi‐quantitative analysis

Abstract: In this work we used a combination of immunogold labelling (IGL) and environmental scanning electron microscopy (ESEM) to detect the presence of a protein on the cell surface. To achieve this purpose we chose as experimental system 3T3 Swiss Albino Mouse Fibroblasts and galectin-3. This protein, whose sub-cellular distribution is still under discussion, is involved in a large number of cell physiological and pathological processes. IGL technique has been utilised by many authors in combination with SEM and TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…In a previous work (Muscariello et al, 2008), we showed that the high resolution power of electron microscopy in ESEM modality is able to evaluate Gal‐3 expression on the cell surface also on Thin‐prep treated human biological samples.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In a previous work (Muscariello et al, 2008), we showed that the high resolution power of electron microscopy in ESEM modality is able to evaluate Gal‐3 expression on the cell surface also on Thin‐prep treated human biological samples.…”
Section: Discussionmentioning
confidence: 82%
“…The first class (0–2 spots/cell) was considered negative (unlabeled sample), since all methods, including ESEM‐IGL, have a percentage of non‐specific labeling (Muscariello et al, 2008). The remaining four classes were obtained assuming a linear progression of about 7 spots/cell.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, ESEM has a wider working space for manipulation comparing with AFM, and the observation is not restricted to the contact with sample. Therefore, ESEM offers new opportunities for single cell analysis at nanoscales [6], [7]. This system has been used to observe and characterize the property of bio samples [8].…”
Section: Introductionmentioning
confidence: 99%